OPTIMALISASI IPAL GEDUNG ARIOBIMO DENGAN MODIFIKASI PROSES LUMPUR AKTIF DAN BIOFILTER - Setiyono, Setiyono (Center for Environmental Technology, 2014)
Ariobimo building, now has a domestic wastewater treatment plant which is equipped with the system re-use. At first, the process of wastewater treatment technology using activated sludge process, while the system re-use of wastewater using a combination of chemical-physical processes, namely the process of coagulation-flocculation followed by sedimentation, filtration and adsorption last with. Because this process is not optimal, then this WWTP outlet and the quality of its water re-use can not meet the expected quality standards. After the improvement of the existing activated sludge process, the quality of this WWTP outlet can meet the quality standards of waste discharges. While the process of coagulation-flocculation is replaced with biofilter process using Ã‚Â honey comb tube media, the quality of the effluent can meet water quality standards.Ã‚Â Keywords :Domestic wastewater,process modification,Ã‚Â water reused.Ã‚Â